1963
DOI: 10.1037/h0046583
|View full text |Cite
|
Sign up to set email alerts
|

Increase over time in the stimulus generalization of acquired fear.

Abstract: Following classical fear conditioning, Ss were trained to jump a hurdle to escape the fear-eliciting stimuli. 2 groups were conditioned in the start box of the hurdle apparatus (Same CB) and 2 in a separate, but similar, conditioning box (Diff CB). Under each condition, 1 group had hurdle training after a 3-min., and the other, after a 24-hr., postconditioning delay. For the 2 Diff CB groups, hurdle training involved a generalized stimulus situation. All groups, except Group 3 min.-Diff CB, learned to jump the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
2

Year Published

1964
1964
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 7 publications
2
73
2
Order By: Relevance
“…If avoidance performance is an indicator of the degree offear elicited by the CS then the improved performance after a long intersession interval in the present study is readily understood. However, in recent studies (McAllister & McAllister, 1963;Saltz & Asdourian, 1963) evidence has been obtained which indicates that the" incubation" effect may be due, not to an increase in fear to the CS, but to increased generalization or spread of fear with time after training. In both studies, it was found that avoidance responding by rats was better 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…If avoidance performance is an indicator of the degree offear elicited by the CS then the improved performance after a long intersession interval in the present study is readily understood. However, in recent studies (McAllister & McAllister, 1963;Saltz & Asdourian, 1963) evidence has been obtained which indicates that the" incubation" effect may be due, not to an increase in fear to the CS, but to increased generalization or spread of fear with time after training. In both studies, it was found that avoidance responding by rats was better 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of reactivity to delayed contextual change occurred in our conditions, whereas the running response was well maintained. The most widely accepted explanation is to consider that the animals forget the initial precise features of the stimulus on which change occurred (pattern of the walls) before they forget the target memory (i.e., the running response) (W. R. McAllister & D. E. McAllister, 1963;Perkins & Weyant, 1958;Spear, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…These data were confirmed by Steinman (1967), who obtained the same results using 1 and 66 days. A disruptive effect on test performance, resulting from a contextual change made only shortly after initial training, has been shown to occur with both appetitive tasks (Perkins & Weyant, 1958;Steinman, 1967) and aversively motivated tasks (Desiderato, Butler, & Meyer, 1966;W. R. McAllister & D. E. McAllister, 1963;Pesselman & Riccio, 1980;Richardson, Riccio, Guanowsky, & Okonkwo, 1983;Seybert, Wilson, & Archer, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, investigations have documented the effect of time on the phenomenon of stimulus generalization: As the temporal interval between training and testing increases, so does the likelihood of responding to a greater range ofstimuli (McAllister & McAllister, 1963;Perkins & Weyant, 1958; D. R. Thomas & Lopez, 1962).…”
mentioning
confidence: 99%